493 THE IMPACT OF PARATRACHEAL LYMPHADENECTOMY ON SURVIVAL AFTER ESOPHAGECTOMY: A NATION-WIDE PROPENSITY SCORE MATCHED ANALYSIS. (17th September 2021) - Hagens, Eliza; Kingma, B; Berge Henegouwen, M; Borggreve, A; Ruurda, J; Hillegersberg, R; Gisbertz, S
Abstract: : Lymph node status in patients with esophageal carcinoma is one of the most important prognostic parameters in esophageal carcinoma. The distribution pattern of lymph node metastases and the optimal extent of lymphadenectomy remains unclear. Therefore the extent of high mediastinal lymphadenectomy, including removal of the paratracheal lymph node stations, in esophageal surgery is a subject of debate. The aim of this study is to investigate the impact of paratracheal lymphadenectomy on survival. Methods: For this nation-wide population-based cohort study, patients with an esophageal or gastro-esophageal junction carcinoma treated by elective transthoracic esophagectomy with two-field lymphadenectomy between 2011 and 2017 were included from the national Dutch Upper Gastro-intestinal Cancer Audit (DUCA) registry. Patients who died within 30 days after surgery or where lymphadenectomy data was missing were excluded from analyses. After propensity score matching patients with adenocarcinoma and squamous cell separately, overall survival was compared between patients who underwent paratracheal lymphadenectomy versus patients who did not. Subgroup analysis was performed in patients with cN0 disease. Results: 3143 patients were included in the DUCA. A total of 512 patients with adenocarcinoma (n = 256 vs. n = 256) and 157 patients with squamous cell carcinoma (n = 62 vs. n = 62) were matched. For both patients with adenocarcinoma and squamous cell carcinoma a paratracheal lymphadenectomy was not significantly associated with longer overall survival (11 versus 10 months, p = 0.209 and 12 versus 11 months, p = 0.206, figure 1). In subgroup analysis, including patients with a squamous cell carcinoma and cN0 disease, paratracheal lymphadenectomy was associated with longer survival (13 versus 9 months, p = 0.011). This was not seen in patients with adenocarcinoma (11 versus 9 months p = 0.263). Conclusion: In both patients with an esophageal adenocarcinoma as squamous cell carcinoma, the addition of paratracheal lymphadenectomy during transthoracic esophagectomy was not significantly associated with longer survival. However, a significantly longer survival was seen in cN0 patients who underwent an additional paratracheal lymphadenectomy, therefore routine removal of paratracheal lymph nodes might still be beneficial. Further studies are warranted with larger subgroups to investigate the impact of an additional (routine) paratracheal lymphadenectomy on survival.